The Awakening - Murphy, Nick; Dooley, Shaun; Hall, Rebecca; Mawle, Joseph; Staunton, Imelda; West, Dominic; Wright, Isaac Hempstead
Parental guidance is advisable for children below 13 years old (PG13)